Engineering the lodging resistance mechanism of post-Green Revolution rice to meet future demands - HIRANO, Ko; ORDONIO, Reynante Lacsamana; MATSUOKA, Makoto (Proceedings of the Japan Academy, Series B, 2017)
Traditional breeding for high-yielding rice has been dependent on the widespread cultivation of gibberellin (GA)-deficient semi-dwarf varieties. Dwarfism lowers the “center of gravity” of the plant body, which increases resistance against lodging and enables plants to support high grain yield. Although this approach was successful in latter half of the 20th century in rice and wheat breeding, this may no longer be enough to sustain rice with even higher yields. This is because relying solely on the semi-dwarf trait is subject to certain limitations, making it necessary to use other important traits to reinforce it. In this review, we present an alternative approach to increase lodging resistance by improving the quality of the culm by identifying genes related to culm quality and introducing these genes into high-yielding rice cultivars through molecular breeding technique.